Liquid composite molding-processing and characterization of fiber-reinforced composites modified with carbon nanotubes - Zeiler, R.; Khalid, U.; Kuttner, Christian; Kothmann, M.; Dijkstra, D. J.; Fery, Andreas; Altstaedt, Volker (AIP Conference Proceedings, 2014)
The increasing demand in fiber-reinforced plastics (FRPs) necessitates economic processing of high quality, like the vacuum-assisted resin transfer molding (VARTM) process. FRPs exhibit excellent in-plane properties but weaknesses in off-plane direction. The addition of nanofillers into the resinous matrix phase embodies a promising approach due to benefits of the nano-scaled size of the filler, especially its high surface and interface areas. Carbon nanotubes (CNTs) are preferable candidates for resin modification in regard of their excellent mechanical properties and high aspect ratios. However, especially the high aspect ratios give rise to withholding or filtering by fibrous fabrics during the impregnation process, i.e. length dependent withholding of tubes (short tubes pass through the fabric, while long tubes are restrained) and a decrease in the local CNT content in the laminate along the flow path can occur. In this study, hybrid composites containing endless glass fiber reinforcement and surface functionalized CNTs dispersed in the matrix phase were produced by VARTM. New methodologies for the quantification of the filtering of CNTs were developed and applied to test laminates. As a first step, a method to analyze the CNT length distribution before and after injection was established for thermosetting composites to characterize length dependent withholding of nanotubes. The used glass fiber fabric showed no perceptible length dependent retaining of CNTs. Afterward, the resulting test laminates were examined by Raman spectroscopy and compared to reference samples of known CNT content. This Raman based technique was developed further to assess the quality of the impregnation process and to quantitatively follow the local CNT content along the injection flow in cured composites. A local decline in CNT content of approx. 20% was observed. These methodologies allow for the quality control of the filler content and size-distribution in CNT based hybrid composites. © 2014 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-20
Keywords: carbon nanotubes (CNTs); filler content analysis; liquid composite molding (LCM); polymer composites; Raman spectroscopy